Swim-specific resistance training - Muniz-Pardos, B.; Gomez-Bruton, A.; Matute-Llorente, A.; Gonzalez-Aguero, A.; Gomez-Cabello, A.; Gonzalo-Skok, O.; Casajus, J. A.; Vicente-Rodriguez, G. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this systematic review was to determine which type of swim-specific training is most beneficial to enhance swimming performance and to determine which specific strength- or power-related tests better predict swimming performance. A search was conducted on PubMed, Cochrane Plus, and SPORTDiscus up to June 2018. Studies were distributed into 2 main categories: swim-specific dry land resistance training (SDLRT) and specific in- water swimming power training (SSWPT). From 1,844 citations, 25 met the inclusion criteria. It was determined that SSWPT was the most appropriate method to improve swimming performance, with tethered swimming protocols being the most studied and effective. In addition, SDLRT was a competent method to enhance swimming performance, and specifically, the inclusion of inertial training might evoke greater improvements in both strength/power capacities and swimming performance, than traditional resistance training. In conclusion, tether forces showed the greatest associations with swimming performance, although the efficacy of tethered swimming as an SSWPT method is yet to be confirmed. Further research should focus on the effects of SDLRT to verify the greater transfer of dry land resistance practices to swimming performance, with inertial training being potentially more beneficial than traditional resistance training.